Stock Returns of Nepalese Commercial Banks: The Role of Size, Book Yield and Earnings Yield - Chaulagain, Rajesh Kumar; Thapa, Bhim Kumar; Paudel, Ramesh Rasik; Subedi, Manoj (Journal of Emerging Management Studies, 2025)
Purpose – This study investigates the factors influencing common stock returns of commercial banks in Nepal’s emerging capital market, specifically analyzing the impacts of bank size (SIZE), book-to-market equity (B/P), and earnings yield (E/P). Empirical study revealed that these factors are directly associated with and influence on common stock returns. Design/methodology/approach – The research adopts a quantitative approach, employing both explanatory and descriptive research design. It analyzes annual data from 19 commercial banks in Nepal over a ten-year period, from 2015 to 2024. Secondary data is collected from the financial statements of concerned banks and their records at the Nepal Stock Exchange (NEPSE). SPSS-26 is employed to perform correlation and regression analyses to examine the relationships between stock returns and key financial variables, including bank size, book yield and earnings yield. Findings – The research shows a positive correlation between SIZE and E/P, while the B/P ratio shows a negative correlation with stock returns of common stocks. The regression analysis reveals that SIZE positively predicts stock returns, and B/P negatively impacts stock returns. However, E/P does not exhibit any ability to predict stock return. Conclusion – The research concludes that larger banks tend to offer higher returns for investors. Nepalese investors consider SIZE and B/P ratio when predicting stock returns. However, investors do not prioritize on bank earnings in their investment decisions. Implications – This study advances the understanding of how E/P, SIZE, and the B/P ratio influence stock returns in Nepalese commercial banks, providing valuable insights for investors and researchers including theoretical implication. Originality/value – The research is original and it emphasizes on all commercial banks listed in NEPSE, analyzing annual dataset covering a decade. This study offers practical implications for portfolio approaches in the context of emerging stock markets.